(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The essay deals with proposed legislations, in Italy and in England, about euthanasia and assistance in dying. It aims to confront the different solutions in both legal systems, for the purpose of finding the best result for the respect of the dignity of people suffering for terminal illness.